China-Focused Organizational Behavior Research 1991—2015 - Godkin, Lynn; Rajamāki, Mikko M. (Journal of Organizational Psychology, 2017)
This study replicates a prior content analysis of China-focused organizational behavior (OB) papers (Godkin, Valentine, Doughty, & Hoosier, 2005) covering the years 1991-2001. It informs four areas of concern: (1) how many studies of management in China have been published in management journals during the period 2002-2015 in comparison to those reported during 1991-2001; (2) the relative increase/decrease in the number of OB studies of China published in management journals over the same periods; (3) the nature and scope of these OB studies of China; and (4) the research gaps in the Chinafocused OB literature that require further inquiry